EFEKTIFITAS MEDIA BIOFILTRASI ANAEROB UNTUK MENDEGRADASI BAHAN ORGANIK PADA LIMBAH CAIR PENCUCIAN IKAN - Tuhu Agung Rahmanto; Umi Hafilda Salamah (EnviroUS, 2022)
This research uses anaerobic biofiltration with various types of media and residence time in a batch system. The purpose of this study was to determine the effectiveness of the anaerobic biofilter reactor in degrading the pollutant load and to find the variation of media type and the best residence time to be continued into a continuous system. From this study, the optimal results obtained in the batch system were BOD 87.4%, COD 89.2%, TSS 87.5% with a residence time of 16 days on the type of bioball media. However, NH3-N cannot be removed under anaerobic conditions, so NH3-N is effective at a residence time of 0 days with an efficiency of 34%. The percentage of removal in the continuous system is stable, that is, the average removal efficiency of BOD is 85.8%, COD is 87.1%, and TSS is 75.8%.